Membangun Generasi Kritis: Peran Literasi Kewarganegaraan dalam Meningkatkan Keterampilan Berpikir Mahasiswa PPKn Universitas Cenderawasih - Lintong, Fikstif Donal; Ginting, Inriyatni Sri Pertiwi (Citra Dharma Cindekia, 2024)
This study examines the role of context-based citizenship literacy in enhancing critical thinking skills among Civic Education (PPKn) students at Universitas Cenderawasih, Papua, Indonesia, addressing the gap between national curriculum and local socio-cultural dynamics. Using a qualitative case study approach, data were collected through in depth interviews, focus group discussions, document analysis, and participatory classroom observations involving 20 students, 5 lecturers, and 3 curriculum stakeholders. Results revealed that 38% of students initially demonstrated high level critical thinking, but participatory learning interventions such as debates on Papua’s special autonomy and local resource conflicts increased systemic analysis skills by 40%. The integration of Papuan cultural elements, fostered inclusive participation and contextual problem-solving. The study concludes that locally adapted citizenship education models significantly strengthen critical thinking while bridging national and regional identities. Practical recommendations include collaborative curriculum design with indigenous communities, replication of the model in marginalized regions, and the incorporation of digital storytelling to amplify skills. This research contributes a novel framework for citizenship education in multicultural contexts, emphasizing reconciliation and equity through pedagogy.